Model Pemanfaatan Bangunan Tradisional Jawa Sebagai Salah Satu Objek Wisata Budaya (Kasus di Kampung Kauman Yogyakarta) - Muhammad Chawari (Berkala Arkeologi, 2004)
The name "Kauman" means the dwelling place of a group of religious experts, where the village is closely related to the existence of the Yogyakarta Sultanate Palace. This palace was founded around 1755, based on the Giyanti agreement which divided the Mataram Kingdom into two, namely the Yogyakarta Sultanate and the Surakarta Sunanate. Meanwhile, the establishment of Kauman Village was not much different from the founding of the Kraton Yogyakarta, because the Grand Mosque which was located in Kauman Village was founded in 1773. Thus, the existence of this village is certainly not much different from the establishment of the Grand Mosque.